P332 is 3D analysis of longitudinal strain useful to predict cardiac events in patients undergoing mitral valve repair?. (17th January 2020) - Volpato, V; Mantegazza, V; Manfredonia, L; Gripari, P; Fusini, L; Tamborini, G; Pepi, M
Abstract: Background: The presence of abnormal 3D left ventricular (LV) strain values in patients diagnosed with mitral valve prolapse (MVP) and significant mitral regurgitation (MR) has been described previously. Recently, some studies showed an addictive prognostic role of Global Longitudinal Strain (GLS) in patients with severe aortic regurgitation. Few data are available about the prognostic role of LV strain in patients diagnosed with severe MR secondary to Myxomatous or fibroelastic deficiency (FED) MVP, undergoing MV repair. Purpose: The aim of the study was to determinate whether LV GLS, strain rate, twist rate and left atrial strain (LAS) may identify a subgroup of patients with MVP and severe MR at higher risk of clinical events after surgical repair in both Myxomatous and FED disease. Methods: We retrospectively studied 100 patients diagnosed with MVP and severe MR due to Myxomatous or FED disease, eligible for MV surgery between 2012 and 2015. Only patients with normal LV function who underwent a 3D transthoracic echocardiographic examination were included. 3D LV GLS, strain rate, twist rate and LAS were measured using 3D analysis software. Clinical data were recorded during a median follow-up of 48 months. Clinical events included cardiac death, arrhythmia and cardiac hospitalization for heart failure or arrhythmic events. Results: 65 patients were diagnosed with Myxomatous and 35 with FED disease. A total of 13 events were recorded during the follow-up, including 1 death, 2 hospitalizations for heart failure and 10 minor arrhythmic events, mostly isolated premature ventricular complex. The number of events was not statistically different between the two groups. In both groups no significant correlation was found between clinical events and each of the echocardiographic parameters measured. Conclusion: In patients with MVP and severe MR but normal LV function, undergoing MV repair, LV strain analysis was not able to predict long term cardiac events., regardless of the etiology.